The Effect of Students 'Reading Ability and Learning Motivation Towards the Ability to Solve Mathematic Stories Story V SD in Padang City year 2019/2020 - Mutiara Kumalasari; Solfema Solfema; Ahmad Fauzan; Farida Farida (International Journal of Educational Dynamics, 2021)
This study aims to determine 1) whether reading ability has an effect on the ability to solve math story problems in grade V SD in Padang teaching 2019/2020; 2) whether there is an effect of student learning motivation on the ability to solve math story problems in grade V SD in Padang City, 2019/2020 teaching; and 3) whether there is an effect of reading ability and student learning motivation on the ability to solve math story problems in grade V SD in the city of Padang teaches 2019/2020. The results showed that the results showed that the effect of reading ability on the ability to solve math story problems was F 23.86> F 4.15. The influence of learning motivation on theme 6 sub-theme 1 learning 4 is F 68.27> F 4.15 and the influence of reading ability and student learning motivation on the ability to solve math story problems F 62.78> F 4.16. So it can be concluded that there is a significant influence between reading ability and student learning motivation on the ability to solve math story problems in 4th grade elementary school students in Padang City 2019/2020.